E-learning Aggregators (An overview of the flaws and improvements) (Trinity Journal of Management, IT & Media (TJMITM), 2022)
COVID-19 has devastated the way things were moving earlier to a forced lockdown, which has badly impacted every domain of life. At the same time, it also opened a floodgate of opportunities in the digital field. The education sector was also not untouched by this digital revolution. Education is an important part of our lives. It was evident that the education sector has seamlessly moved digital/online. In particular, the COVID-19 outbreak has given opportunities to learners, students, and academicians to learn at their own pace with comfort and acquire skills and certifications through various courses available and offered online via multiple digital platforms. Now, there is a flood of platforms, courses, teachers, and learners as well. Due to the ample number of online platforms, it is now creating chaos among learners trying to find suitable ones.Additionally, learners spend a lot of time browsing across many websites and platforms, maybe because inadequate tools are present that allow for all comparisons to be made in one location. Although students and learners were already taking online courses, a greater number of them have been signing up for them since COVID-19. The availability of numerous platforms on the internet that provide a variety of courses has left learners perplexed about how to find one that will be recognized in the business world and by academic institutions, but this is mainly because they lack the right tools and knowledge. Eventually, students end up taking or enrolling in a course that is either really basic or possibly too advanced for them. The answers can't be located in one spot, which is a problem for the students. As students, the same problem was faced by us also. We, thus, after identifying the problem, looked for solutions and found a few, but even those solutions were not fulfilling our requirements. Thus, this paper includes an overview of some of the solutions that aim to solve the problem of learners by allowing them to easily find courses and platforms that are appropriate for them in one place without wasting time browsing multiple websites. Discussions will also include all of the platforms' potential improvement areas.
Keywords: e-learning; education; course aggregators; MOOC aggregators; learning providers